Ambipolar Interfacial Molecule for Enhancing Performances of Perovskite Solar Cells with Versatile Architectures Under Various Illumination Environments - Choi, Min Jun; Lee, Seok Woo; Shim, Hongjae; Shin, So Jeong; Chun, Hye W.; Yoon, Sang Eun; Prayogo, Juan Anthony; Seidel, Jan; Yun, Jae Sung; Chang, Dong Wook; Kim, Jong H. (Advanced Energy Materials, 2025)
Perovskite solar cells (PSCs) are of significant interest for researchers as the next-generation energy harvesters. However, PSCs suffer from traps that are densely distributed at interfaces, which deteriorate the device's performance. To address this issue, a new small molecule (DTAQTPPO) capable of trap passivation on the perovskite layer surface while possessing ambipolar charge extraction properties is designed, which endow DTAQTPPO with dual functionality as both interface defect passivator and efficient hole/electron extractor in both n-i-p and p-i-n architectures. These beneficial effects improve the power conversion efficiencies (PCEs) of PSCs to 23.03% and 23.55% under 1 sun and to 37.18% and 36.29% under 1000 lux light-emitting diode (LED) indoor illuminations for both n-i-p and p-i-n architectures, respectively, after incorporating DTAQTPPO. In addition, ambipolar DTAQTPPO enhance the PV properties of PSCs using an anti-solvent-free perovskite layer with a PCE of 23.24% and indoor PCE of 35.47% under 1 sun and LED 1000 lux illumination, respectively. These results suggest that DTAQTPPO can be widely used as a multifunctional interlayer to improve the PCE of PSCs with versatile device architectures under various light illumination conditions and generality for different perovskites and processes.
Keywords: Ambipolar; Ambipolar properties; Illumination environment; Interface defect passivations; Interfacial molecules; Lightemitting diode; Performance; Perovskite layers; Power conversion efficiencies; Versatile device structure; ambipolar properties; illumination environments; interface defect passivation; perovskite solar cells; versatile device structures